Sero-prevalence and factors associated with anti-Brucella antibodies in slaughter livestock in Uganda - Bugeza, James; Roesel, Kristina; Moriyon, I.; Mugizi, Denis; Alinaitwe, Lordrick; Kivali, Velma; Kankya, C.; Cook, Elizabeth A.J. (Frontiers Media, 2023)
Introduction: Brucellosis is endemic in Uganda and is a major cause of production losses in livestock. Early detection and quantification of the disease is vital for its control and eradication. The aim of this study was to assess the sero-prevalence and factors associated with anti-Brucella antibodies in slaughtered livestock.